1977
DOI: 10.1111/j.1651-2227.1977.tb07926.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Negative Chest‐wall Pressure Therapy for Assisting Ventilation in Older Children With Progressive Respiratory Insufficiency1

Abstract: Continuous negative chest-wall pressure (CNP) was used to assist ventilation in 14 children, 6 months to 14 years of age, who had progressive respiratory insufficiency caused by diffuse bilateral alveolar disease. Before the start of CNP therapy, each child had a respiratory rate greater than 50/min, arterial oxygen tension (PaO2) less than 70 mmHg (FIO2 greater than or equal to 50%), and arterial carbon dioxide tension (PaCO2) less than 45 mmHg. The mean intrapulmonary right-to-left shunt was 28.7 +/- 3.8%. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…20,21,22,23,24 Studies have shown an improved quality of life and physical activity and improvements in blood gases when these patients were managed on non-invasive techniques. 20 Jackson et al investigated the long-term (5 yr) effectiveness of cuirassassisted ventilation in patients with chest wall disease and neuromuscular disorders.…”
Section: Cnep In Neuromuscular Disordersmentioning
confidence: 98%
“…20,21,22,23,24 Studies have shown an improved quality of life and physical activity and improvements in blood gases when these patients were managed on non-invasive techniques. 20 Jackson et al investigated the long-term (5 yr) effectiveness of cuirassassisted ventilation in patients with chest wall disease and neuromuscular disorders.…”
Section: Cnep In Neuromuscular Disordersmentioning
confidence: 98%